DEVELOPMENT OF EVALUATION WITH WARDWALL MEDIA ON ARABIC SUBJECTS CLASS VII E SMPIT INSAN MULIA BOARDING SCHOOL PRINGSEWU - Oktaviani, Margi; Salamun, Salamun; Hamid, Abdul (Jurnal Pendidikan Bahasa Arab L-DHAD, 2024)
Abstract (The application of games with the wordwall method is one alternative to be a medium for evaluating students Arabic language learning. The background of the problem of this study is the use of inappropriate evaluation methods in learning which results in students obtaining low scores and for teachers filing evaluation results in offices that accumulate after evaluating Arabic language learning. Even some students consider that the final evaluation of learning Arabic is a scary and horror-like learning. This resulted in low scores of students on the evaluation of Arabic language learning. Therefore, it is necessary to conduct research to increase student interest in learning evaluation by using wardwall media that can increase the value of student learning evaluation and the practicality of evaluating evaluation. This study used Classroom Action Research (PTK) with the second cycle. Each cycle consists of six stages: problem identification, needs assessment, ideas, implications, and decision making. The subjects of the study were 21 students of class VII E SMPIT Insan Mulia Boarding School Pringsewu. This is shown by an increase in final grades with a percentage in cycle I of 29% in cycle II of 100%, and reduced evaluation filings on teachers' desks. So that the results of the study showed that the results of the evaluation of Arabic learning were able to increase students' final grade).